ANALISIS SUMBE DAYA ALAM DESA PANTE DEERE DALAM MENDUKUNG EKONOMI MASYARAKAT PESISIR DAN PENGUNUNGAN - Maria Bainhana; Lea Priska Adangdjaha; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to describe how the natural resources of Pante Deere Village are utilized and to examine the extent to which these potentials contribute to the local economy of communities living in two distinct geographical areas, namely the coastal and mountainous regions. Pante Deere Village possesses diverse natural resources that are used by residents as both primary and supplementary sources of livelihood. In the coastal area, economic activities rely heavily on fishing, the processing of various marine products, and the use of resources such as agar-agar. Meanwhile, communities residing in the mountainous region depend more on forest products and plantation commodities, particularly candlenut, which serves as a leading commodity and provides significant economic contributions to households and the wider community.